Estudio comparativo del efecto clínico producido por el first class y el péndulo en pacientes atendidos en la facultad de odontología de la Universidad de Antioquia. Análisis radiográfico y de modelos (2007)
ABSTRACT: The purpose of this research was to establish and compare the clinical and radiographic results obtained during the four month use of the pendulum and the First class® in relation with its craneofacial, dental, and soft tissue effects in patients who had indicated as part of their treatment plan, a distalization of their first upper molars. The sample consisted of 27 subjects between 12 and 17 years of age: 11 treated with pendulum, 8 treated with First class®, and 8 controls to discard any changes due to growth. All patients received inicial Panoramic X-rays, inicial and final lateral cephalograms; 1:1 standardized pictures of study casts at the beginning, second and fourth months of treatment. The radiographic results showed there were no significant changes in the skeletal structures. At the dento-alveolar level an average molar distalization of 4.68 ± 4.9 mm was observed with the pendulum and of 2.05 ± 4.06 mm with the First class® both of which were accompanied by distal inclination (12.2º pendulum, 3.2º First class®) and intrusion (0.55 and 0.037 mm respectively) with an assymetric right – left behavior. For each millimeter of molar distalization there was an increment in incisal labialization of 0.9º with the pendulum and 3.0º with the First class® accompanied by a decrease in the nasolabial angle (-5.45º with the pendulum and -6.0º with First class®) and an upper lip protrusion (1.59 and 1.07 mm respectively). The dental casts showed a rotational change in the molar with a heterogenous behavior; with both pendulum and First class®, rotations in opposite directions were observed: distopalatal (+) y distolabial (-). The total average was positive in both, being greater for the First class® (5.87°) than for the pendulum (4.3°), conserving a right-left asymmetric pattern. The effectiveness of the anchorage offered by the palatal acrylic button should be questioned, since there was evidence of anterior displacement of this structure with a negative labialization effect on the anchorage teeth.